Conductive polymer composites from polylactic acid/Natural rubber filled with carbon black - Buys, Yose Fachmi; Lokman, Nor Afiza Syafina (2014)
In order to develop environmentally friendly conductive polymer composites, polylactic acid (PLA) was melt blended with natural rubber (NR), with addition of carbon black (CB) as the conductive filler. It was found that the PLA/NR blends were immiscible, and the sea-island and co-continuous morphological structures were observed at PLA/NR with ratio of 80/20 vol% and 60/40 vol% respectively. Addition of CB to 60/40 PLA/NR matrix, brought the composites to become electrically conductive at CB content of 2 phr. It was also found that the impact strength of PLA/NR/CB composite is better than that of the neat PLA.